Flexible carbon nanotube papers with improved thermoelectric properties - Zhao, Weiyun (2013)
Although theoretical calculations indicate that the thermoelectric figure of merit, ZT, of carbon nanotubes (CNTs) could reach >2, the experimentally reported ZT values of CNTs are typically in the range of 10−3–10−2, which is not attractive for thermal energy conversion applications. In this work, we report the preparation of flexible CNT bulky paper for thermoelectric applications. The ZT values of the CNT bulky papers could be significantly enhanced by Ar plasma treatment, i.e. increasing it from 0.01 for pristine CNTs to 0.4 for Ar-plasma treated CNTs. The improved thermoelectric properties were mainly due to the greatly increased Seebeck coefficients and a reduction in the thermal conductivities, although the electrical conductivities also decreased. Such an improvement makes the plasma treated CNT bulky papers promising as a new type of thermoelectric material for certain niche applications as they are easily processed, mechanically flexible and durable, and chemically stable.